'Ulum Al-Qur’an: Discourse Nasikh-Mansukh Syahrur's Perspective - Mia Fitriah El karimah (Proceeding International Conference on Religion, Science and Education, 2023)
In the course of history 'Ulum al-Qur'an has a record of quite long and tough debates, especially regarding the concept of nasikh-mansukh. This controversy actually occurred because of the debate by the 'ulama regarding, are there any verses of the Koran that are scripted and there is no consensus of opinion in understanding the word text itself. Because of this, a contemporary scholar emerged, namely Muhammad Syahrur who tried to reconstruct this discourse by presenting the concept of nasikh-mansukh in his perspective and how it implies for the interpretation of legal themes. The fiqh he put forward. The purpose of this study is to find out Syahrur's views on the concept of nasikh-mansukh and its implications for the interpretation of legal themes of fiqh. This study uses a descriptive analysis method with qualitative data types. The research data was obtained through text review (reading text) and then analyzed, namely the exposition of what is in a text by describing it in the author's language. And supported by primary data in the form of a book - the work of Muhammad Syahrur - itself and secondary data, namely from books, books, journals, and other scientific writings that are in accordance with the problem studied. The data collection technique used in this research is text analysis or documentation or it can be called library research and book survey techniques. As for the results of this study, Muhammad Syahrur who argues that the nasikh-mansukh theory is the abolition of the previous syari'at by replacing it with the Prophet Muhammad's shari'at. He is more of the opinion that the abolition (naskh) in the nasikh-mansukh theory is the abolition of the treatises and shari'ah of the previous Prophet and replaced with the shari'ah of the Prophet Muhammad, whether it is in the form of refinement or replacement. According to him, it is impossible to replace the verses that contain the same syari'at for the same apostle, but there must have been a replacement of the syari'at between different syari'at and the messengers who came successively.